Ethics of Public Administration in The Administration of Governance in Indonesia - Zaidan Nawawi (MAP Program Pascasarjana Universitas Sjakhyakirti, 2018)
Ethics is an important element which determines the successful implementation of organizations activities and public administration actors. The importance to implement public administration ethics in the Indonesia government bureaucracy was based to the ethical problems which happened, such as corruption, collusion and nepotism. This research used qualitative method, where is primary data obtained from observations, and secondary data obtained from media and literature study. From the research that has been conducted, it is known that few of government officials in Indonesia are lack of accountability in performing their duties, authorities and responsibilities and as a result the public bureaucracy in the reform era was much highlighted by the public and got criticism. To solve this problem, besides by enforcing the laws, the government also must to cultivate and implement the public administration ethics for their bureaucratic apparatus.